Calcium‐Independent Activation of an Allosteric Network in Langerin by Heparin Oligosaccharides. (29th March 2017) - Hanske, Jonas; Wawrzinek, Robert; Geissner, Andreas; Wamhoff, Eike‐Christian; Sellrie, Katrin; Schmidt, Henrik; Seeberger, Peter H.; Rademacher, Christoph
Abstract: The C‐type lectin receptor Langerin is a glycan‐binding protein that serves as an uptake receptor on Langerhans cells and is essential for the formation of Birbeck granules. Whereas most Langerin ligands are recognized by a canonical Ca 2+ ‐dependent binding site, heparins have been proposed to make additional contacts to a secondary, Ca 2+ ‐independent site. Glycan array screening and biomolecular NMR spectroscopy were employed to investigate the molecular mechanism of these interactions. We observed that binding of heparin hexasaccharides to a secondary site did not require the presence of Ca 2+ and activated a previously identified intradomain allosteric network of Langerin (thus far only associated with Ca 2+ affinity and release). We propose a communication hub between these two binding sites, which sheds new light on modulatory functions of Langerin–heparin interactions. Abstract : Pick a site : After glycan array screening, the interactions of heparin oligomers with human Langerin were investigated by 1 H, 15 N HSQC NMR and 19 F NMR. Evidence for a secondary, Ca 2+ ‐independent binding site in the protein's carbohydrate recognition domain was found—potentially involved in the formation of Birbeck granules and consequently immune modulation.